Transmission Outage Cost Analysis Using Value of Loss Load Approach Based on Macro Economic Data - Suwargono, Son; Garniwa, Iwa (Universitas Indonesia, 2024)
The West Nusa Tenggara (NTB) electricity system, which consists of the Lombok System and the Sumbawa-Bima System, has an important role in supporting the country's economy, especially in the tourism segment. Quantitatively, there has been no measurement of the impact of electricity disruption on the macro economy. Value of Loss Load (VoLL) is a useful quantity parameter in the economic evaluation of electric power systems. It can be represented as the value of losses borne by customers in case of electricity service interruptions. For policy makers and electricity management, the size of the VoLL would affect decisions regarding investment. A low VoLL requires for a low reliability level and a high VoLL for a high reliability level. This research will calculate Transmission outage costs using the Value of Loss Load approach based on macro economic data and predicting VoLL 2024 - 2030. The outcome of the research shows that The Lombok System VoLL is lower than Bima – Sumbawa System. Outage costs due to disruptions on the Transmission System side affect GDP by 0.001% / year. The trend of VoLL 2024 – 2030 is estimated to decrease by an average of 2.29% / year which is indicate it is is inline with Rencana Usaha Penyediaan Tenaga Listrik 2021 - 2030.